A Gadamerian approach to interpreting pain: model-making metaphors through embodied cognitive theory. Issue 4 (1st October 2016) - Marsh, Peter; Chubb, Shirley; Saber-Sheikh, Kambiz; Hooker, Charlie; Moore, Ann
ABSTRACT: This paper will discuss how the conceptualization of embodied, abstract notions such as pain, which is multi-modal, non-visual and subjective, has the potential to be communicated visually using model making, as it is traditionally understood in the fields of architecture and design. We propose a new methodological approach to research where Gadamer's [2004. Truth and Method . Continuum International Publishing Group] understanding of intersubjective interpretation used in conjunction with Simulation theory [Gallese, V., and A. Goldman. 1998. "Mirror Neurons and the Simulation Theory of Mind-Reading." Trends in Cognitive Sciences 2 (12): 493–501] in embodied cognitive science, provides a strong framework in which to formulate a palette of materials and forms to visualize subjective experience. This novel approach to design research is currently being undertaken within the field of Health Sciences to produce metaphorically provocative, descriptive models of the lived experience of people with Rheumatoid Arthritis (RA) to help bridge the gap in understanding between the sufferer and the public. This paper seeks to engage briefly with two questions integral to the research being undertaken: how does one understand another's pain, and how can one conceptualize and communicate abstract notions such as pain visually using material and form as language?